Analisis Penjadwalan Proyek Menggunakan Metode Repetitive Scheduling Method (RSM) - Amiano, Stevan Febrian; Apria Brita Pandohop Gawei; Dewantoro; Veronika Happy Puspasari; Almuntofa Purwantoro (Jurnal Serambi Engineering, 2025)
Effective scheduling is a key factor in the success of construction projects. The Repetitive Scheduling Method (RSM) is a scheduling method designed for projects with repetitive activities, such as housing developments, high-rise buildings, highways, or bridges. This study aims to analyze the application of the RSM method in the Menteng VIII Housing Project in Palangka Raya. By comparing the project duration and cost before and after the implementation of RSM, this study found that the project duration could be reduced by 33.33%, from 231 days to 154 days, resulting in a total labor cost savings of IDR 15,700,000 per housing unit. These results demonstrate the effectiveness of RSM in improving time and cost efficiency in construction projects. The study also emphasizes that RSM reduces workers' idle time, increases productivity, and maintains work continuity. The application of RSM in this project is expected to serve as a reference for construction project managers in selecting a more optimal and efficient scheduling method. Thus, RSM can be one of the best alternatives in scheduling projects with repetitive work patterns.